2008
DOI: 10.1038/ki.2008.451
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt regulates the phosphorylation of OSR1/SPAK kinases and the sodium chloride cotransporter through aldosterone

Abstract: Pseudohypoaldosteronism type II (PHAII) is caused by mutations in the WNK1 and WNK4 genes (WNK with-no-lysine kinase). In a mouse model of this disease where a mutant of Wnk4 D561A was knocked in, increased phosphorylation of the sodium chloride cotransporter (NCC) was found and the transporter was concentrated on the apical membrane of the distal tubules. In addition, we recently found that other kinases, such as the oxidative stress response kinase-1/STE20/SPS1-related proline alanine-rich kinase (OSR1/SPAK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
199
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(225 citation statements)
references
References 29 publications
22
199
3
1
Order By: Relevance
“…A recent study also showed that WNK4 increases the association of NCC with AP3 to promote NCC delivery to the lysosomal compartment for degradation, 40 which is consistent with our conclusion. Our findings further support the notion that NCC is regulated through affecting its forward trafficking in addition to other mechanisms such as altering its abundance, [41][42][43] glycosylation, 10 and phosphorylation. 44,45 In the kidney, NCC is exclusively expressed in DCT and responsible for 5 to 7% of sodium reabsorption.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A recent study also showed that WNK4 increases the association of NCC with AP3 to promote NCC delivery to the lysosomal compartment for degradation, 40 which is consistent with our conclusion. Our findings further support the notion that NCC is regulated through affecting its forward trafficking in addition to other mechanisms such as altering its abundance, [41][42][43] glycosylation, 10 and phosphorylation. 44,45 In the kidney, NCC is exclusively expressed in DCT and responsible for 5 to 7% of sodium reabsorption.…”
Section: Discussionsupporting
confidence: 76%
“…46 It is likely that, under normal physiologic conditions, NCC constantly traffics to both the plasma membrane via a secretory pathway and the lysosome for degradation to maintain its basal steady protein level, which is subject to regulation by many mediators. 3,6,10,[41][42][43][44][45] Renal DCT cells contain endogenous WNK4 kinase. 2 In the presence of WNK4, the rate of NCC targeting to the lysosomal compartment is much higher than that of NCC without WNK4.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the NaCl cotransporter (NCC) in the DCT perturbs BP not only in the extreme phenotypes of patients with Gitelman's 1 and Gordon's 2 syndromes but also in healthy individuals, 3 and the inhibition of NCC by thiazide diuretics has a potent antihypertensive effect. 4 In the short term, NCC activity is regulated at the molecular level; neurohormonal inputs converge on intracellular signaling networks (WNK-SPAK/OSR1 5 and SGK1/Nedd4-2 pathways 6 ) that shuttle NCC to and from the plasma membrane 7 and induce posttranslational protein modifications that modify transport function (phosphorylation 8 and ubiquitylation 6 ). Sustained physiologic perturbations promote structural remodeling of DCTepithelium.…”
Section: Namentioning
confidence: 99%
“…To date, we have identified several upstream regulators for WNK kinases, including hormonal factors, such as aldosterone, angiotensin II (AngII), insulin, and vasopressin. [7][8][9][10][11] However, the mechanisms of signal transduction from these factors to WNK kinases have not necessarily been clarified. We speculated that one of these regulations could be mediated by the ubiquitination of WNKs by KLHL2 and/or KLHL3.…”
mentioning
confidence: 99%